Exploring the Use of Virtual Reality for the Delivery and Practice of Stress-Management Exercises - Soh, Desmond Jun Hong; Ong, Crystal Huiyi; Fan, Qianqian; Seah, Denise Ju Ling; Henderson, Stacey Lee; Jeevanandam, Lohsnah; Doshi, Kinjal (Frontiers in Psychology, 2021)
Background Mindfulness-based interventions may benefit healthcare professionals with burnout symptoms. Virtual reality (VR) may reduce initial difficulty of engaging in mindfulness exercises and increase participants’ engagement through immersion and presence. Aim The aim was to investigate how VR affects participants’ experience of engagement with mindfulness practice, and its impact on quality of practice and negative mood states. Methods Fifty-one healthcare professionals were randomized to receive either a visualization or non-visualization mindfulness practice, to compare the quality of practice through the use of audio only vs. with a virtual reality interface. Selected self-reported measures were collected during the session (immersion, quality and difficulty of practice, mood states and likelihood for future practice). Results Results showed that order instead of type of modality administered made a difference in quality of mindfulness practice. A greater sense of presence was reported with VR if administered after audio (F = 4.810, p = 0.033, Partial η2 = 0.093). Further, participants described difficulty practicing with audio if administered after VR (F = 4.136, p = 0.048, Partial η2 = 0.081). Additionally, lower mood disturbance was reported with VR if administered after audio (F = 8.116, p = 0.006, Partial η2 = 0.147). Qualitative responses echoed a preference for VR to engage better, in addition to improved mood states after practice. Conclusion Findings suggest that VR has the potential to provide healthcare professionals with an alternative or a supplement to conventional mindfulness practice.